STRATEGIC PLANNING AND SUSTAINABLE DEVELOPMENT IN SPANISH CITIES - J. GONZÁLEZ, María; L. DE LÁZARO, María (European Journal of Geography, 2013)
The paper investigates how decision-making processes relating to strategic urban projects are framed in order to achieve innovative urban sustainable development and contextualize the problems which appear in the ten cities chosen as models (those with the highest populations). A sustainable city is one that has undertaken a coherent path towards not only strictly environmental topics but also themes like economic growth models and citizens’ rights, addressing fundamental issues that are interconnected. These are mainly land use, natural resources and mobility, social cohesion and inclusion projects, expanding information and communication technologies. The aim of this work is to discuss these clearly related themes from a standpoint of sustainable development and strategic planning. In recent years there has been a growing interest in sustainable development as a guiding principle to allow the integration of economic development and the environment within policy and strategy